Performance of Doppler-Based Resistive Index and Semiquantitative Renal Perfusion in Predicting Persistent Acute Kidney Injury According to Operator Experience: Post Hoc Analysis of a Prospective Multicenter Study*. Issue 4 (25th October 2021) - Saade, Anastasia; Bourmaud, Aurelie; Schnell, David; Darmon, Michael; ,
Abstract : OBJECTIVES: The Doppler-based resistive index and semiquantitative evaluation of renal perfusion using color Doppler failed to discriminate renal recovery patterns in a recent study. The influence of operator experience on resistive index and semiquantitative evaluation of renal perfusion performances is however unknown. This study aimed at evaluating the performance of resistive index and semiquantitative evaluation of renal perfusion according to the operator experience to predict short-term renal prognosis in critically ill patients. DESIGN: Preplanned ancillary analysis of a prospective multicenter cohort study. SETTING: Seven ICUs. PATIENTS: Unselected ICU patients. INTERVENTION: Renal Doppler was performed at admission to the ICU. The diagnostic performance of resistive index and semiquantitative evaluation of renal perfusion to predict persistent acute kidney injury at day 3 was evaluated. MAIN RESULTS: Overall, 371 patients were included, of whom 351 could be assessed for short-term renal recovery. Two thirds of the included patients had acute kidney injury ( n = 233; 66.3%), of whom 136 had persistent acute kidney injury (58.4%). Overall performance in discriminating persistent acute kidney injury was however null with an area under the receiver operating characteristic curve less than 0.6 for both resistive index and semiquantitative evaluation of renal perfusion, and no difference across operator experience. A multivariate analysis using logistic regression with the center as a random effect adjusted on the operator experience showed no association between resistive index (odds ratio, 0.02 per international units (95% CI, 0.00–18.60 international units]) or semiquantitative evaluation of renal perfusion (odds ratio, 0.96 per international units [95% CI, 0.43–2.11 international units]) and persistent acute kidney injury. Similar results were obtained within subgroups of expert and nonexpert operators. CONCLUSIONS: Doppler-based measurements performed by an expert or a nonexpert operator did not discriminate renal recovery patterns and neither modified the risk stratification of acute kidney injury persistence.